Pengaruh Komunikasi Dan Disiplin Terhadap Kinerja Karyawan Pada PT Amartha Boga Lestari Bintaro - Wahyuningsih, Sri; Tarwijo Tarwijo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Business competition has now entered a free market without boundaries, so every company must make every effort to survive and avoid bankruptcy. To face this competition, organizations need to have competent human resources so that the quality of the company can improve. PT Amartha Boga Lestari Bintaro has also experienced this. This study aims to determine the effect of communication and discipline on employee performance at PT Amartha Boga Lestari Bintaro. A quantitative method was used with all 60 employees as the sample. The results show that partially, communication (Y = 5.285 + 0.865 X1, r = 0.748, t = 3.947 > 2.00172, p < 0.05) and discipline (Y = 5.667 + 0.866 X2, r = 0.832, t = 6.857 > 2.00172, p < 0.05) have a positive and significant effect on performance. Simultaneously, communication and discipline also have a significant effect (Y = 1.153 + 0.400 X1 + 0.626 X2, r = 0.871, R² = 75.8%, F = 89.393 > 3.16, p < 0.05), confirming that these two variables are important in improving employee performance.